Literature review on fermentation factors of restaurant organic waste affecting feed quality - Yuli Andriani; Anggi Adrian Hutapea; Irfan Zidni; Walim Lili; Muhamad Fatah Wiyatna (Depik, 2021)
The high level of public consumption, balanced with the increasingly dense population globally, makes food waste more and more. Food waste is the second-largest contributor to waste in the world. Moreover, the lack of food waste management makes this condition even worse. This food waste can be found, one of which is in restaurants, school canteens, food courts, and others. Fermentation is the process of breaking down complex substances into simpler ones. A fermentation process can help process food waste into various products such as liquid organic fertilizer, compost, biogas, and raw material for fish feed. Through the fermentation process, food waste can be used as an alternative fish feed with high nutritional content to benefit fish cultivators. Fish need many nutrients for their bodies, with food waste that has been processed will meet the dietary needs of fish. The cultivators will benefit more from the cost of feed and the sale of fish that can meet consumer needs.Moreover, the demand for the fish market is increasing every year. Several factors play a role in the success of the food waste fermentation process and the quality of the resulting product to be converted into fish feed raw materials. These factors include incubation time, pH acidity, and microbial factors that can accelerate the spoilage of fish feed raw materials.Keywords:Fermentation,Restaurant wasteFish feedFactorsQuality of feed IngredientsLiterature review on fermentation factors of restaurant organic waste affecting feed quality